KULIAH KERJA NYATA (KKN) DI DESA SUNGAI NAMANG KECAMATAN DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA - Norhidayah Norhidayah; Herlina Novita Sari, Maya Fitria, M. Bahruddin, Akhmad Mutawali, Maskanah, Annisa Rahmah, Noviawati, (Adiba Aisha Amira, 2021)
The transfer of knowledge from student lecturers who are considered to be still lacking in equipping students to go directly into social life after graduation becomes the STAI Rakha Amuntai party to carry out real work lectures as well as one of the obligations of the tri dharma of higher education. The results of the Real Work Lecture (KKN) in Sungai Namang Village, Danau Panggang Subdistrict, are: First, the STAI Rakha Amuntai KKN for the Academic year 2022 – 2023 is felt to be quite successful and smooth in achieving the goals that have been programmed. Second, the implementation of KKN for two months is still felt to be narrow if it is associated with the density of the program being implemented. Third, thanks to the assistance of the Village Head and all of his apparatus as well as the residents of Sungai Namang Village, they were able to carry out all the programs to be implemented. Fourth, by holding KKN by STAI Rakha Amuntai, we have learned a lot of lessons that can be drawn from the KKN.